Cenários para a reduç\~ao dos custos de comércio no Mercosul: Efeitos sobre o comércio regional e mercado de trabalho brasileiro - Flávio Lyrio Carneiro (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– We estimate the effects of reductions in trade costs between the four original members of Souther Common Market (Mercado Común del Sur - Mercosur) on regional trade and on the Brazilian labor market, using the model developed by Caliendo, Dvorkin e Parro (2019), which features elements such as labor market frictions and input-output linkages. Two counterfactual scenarios about the evolution of trade costs in Mercosur countries are considered. Results suggest that efforts to reduce trade costs can have starkly different effects on regional trade, depending on its geographic coverage: reductions that are limited to transactions among the four countries leads to a substitution between domestic production and intra-bloc trade, with limited effects on extra-bloc trade flows, while general reductions in trade costs of the four countries also affect trade with extra-Mercosur partners. The effects on Brazilian labor market are also different among scenarios, but small in magnitude in both cases.
Keywords: F11; F14; F15; F16; 330; international trade; trade integration; labor market dynamics; general equilibrium